Interaction of anaesthetics with the carotid body glomus cell and the background potassium channel response to hypoxia - O'Donohoe, P; Pandit, J; Buckler, K; Dorrington, K; Kumar, P (2015)
This thesis investigates the role anaesthetics play in the depression of the acute hypoxic and hypercapnic ventilatory response. Particular attention is paid to TASK (TWIK related acid sensitive potassium) channels that are known to be sensitive to both hypoxia and the volatile anaesthetics. After chapters relating to a general introduction and methods, chapter 3 describes studies into the hypoxic and hypercapnic responses of mice with genetic ablation of TASK 1 and/or TASK 3. By using whole animal unrestrained plethysmography, it was demonstrated that any loss of TASK channels resulted in a depression of ventilatory responses to hypoxia and hypercapnia. In isocapnic hypoxia, there is a genotype specific depression by anaesthetics of the remaining AHVR, depending on whether halothane or isoflurane is inspired. Chapter 4 establishes that propofol depresses the chemosensory responses of carotid body glomus cells. Using ratiometric flurimetry to measure the intracellular calcium concentration in isolated neonatal rat glomus cells, it was demonstrated that propofol depresses the normal cellular response to both hypoxia and hypercapnia. Using pharmacological modulators of GABA and nAChR, and single channel patch clamp electrophysiology of TASK, it is apparent that this depression is independent of these candidate mechanisms. Chapter 5 describes the effects of the anaesthetic dexmedetomidine at two levels of the hypoxic chemoreflex arc in rodents. Neither isolated rat glomus cells, nor unrestrained mice show significant depression of hypoxic responses when dexmedetomidine is present. Chapter 6 illustrates the potential role for specific antagonism of TASK channels in stimulating the carotid body. Two TASK channel blockers, A1899 (TASK 1 antagonist) and PK-THPP (TASK 3 antagonist) are shown to cause a significant influx of calcium into isolated glomus cells, and an augmentation in the glomus cell response to hypoxia, which persists in the presence of isoflurane. Overall, this thesis provides evidence that both TASK 1 and TASK 3 channels are essential for normal hypoxic chemosensitivity. It has extended the knowledge that anaesthetics depress glomus cell chemosensation, by demonstrating that propofol too causes this effect. It also proposes that dexmedetomidine may have greater utility in sparing of ventilatory reflexes. By selectively blocking TASK channels, glomus cells can be stimulated, and exploiting this mechanism would be useful in minimising anaesthetic-induced depression of ventilation.